Association between syndecan-1 and renal function in adolescents with excess weight: evidence of subclinical kidney disease and endothelial dysfunction - Saboia,Z.M.R.M. (2018)
Excess weight (overweight and obesity) is associated with kidney and cardiovascular disease. The aim of this study was to investigate the association between syndecan-1 and renal function among adolescents with excess weight. A total of 56 students from a public school at Fortaleza, CE, Brazil, were investigated. The adolescents were submitted to anthropometric evaluation, including weight, height, blood pressure and body mass index. Blood and urine samples were collected for the determination of serum lipids (total cholesterol, high density lipoprotein cholesterol, low density lipoprotein cholesterol, triglycerides), and the endothelial injury biomarker syndecan-1. Participants' mean age was 16±1 years (range 14-19 years), and 68% were females. Overweight was observed in 4 cases (7.1%) and obesity in 7 (12.5%). Changes in serum lipid levels were more frequent in the overweight group. A positive correlation between syndecan-1 and serum creatinine (r=0.5, P=0.001) and triglycerides (r=0.37, P=0.004), and a negative correlation with glomerular filtration rate (r=-0.33, P=0.02) were found. These findings suggest that adolescents with excess weight present incipient changes at the cellular level that make them more vulnerable to the development of kidney and cardiovascular diseases.